Luminescent Zn (II)-Based Nanoprobes: A Highly Symmetric Supramolecular Platform for Sensing of Biological Targets and Living Cell Imaging - Diana, Rosita; Sessa, Lucia; Concilio, Simona; Piotto, Stefano; Panunzi, Barbara (Frontiers in Materials, 2021)
Zinc (II) cation is an environmentally friendly metal, less expensive, easy to dispose of, and managed. Highly engineered symmetric systems can be built using zinc (II) atoms as the metal nodes of hybrid organic-inorganic supramolecular structures. In biological contexts, luminescent zinc-based nanoprobes are in growing demand. Specifically, they are currently employed to detect biologically and environmentally relevant analytes, in therapeutic drug delivery, and for bioimaging and diagnostic techniques monitoring aspects of cellular functions. This review will provide a systematic and consequential approach to zinc-based nanoprobes, including zinc-based MOFs and other zinc-based organized nanoparticles. A progression from detecting the biological target to the intracellular sensing/marking/carriage has been followed. A selection of significant cutting-edge articles collected in the last five years has been discussed, based on the structural pattern and sensing performance, with special notice to living cell bioimaging as the most targeted and desirable application.